Major depressive disorder in post-secondary students attending foodbanks in France - Rambliere, Lison; Leservoisier, Clémentine; Bedo, Ysé; Macalli, Melissa; Lebugle, Amandine; Douay, Caroline; Guénée, Lorraine (Frontiers in Public Health, 2023)
Introduction: Poor mental health among youth is a major public health issue that has risen to the forefront since the Covid-19 crisis, especially among post-secondary students and precarious populations. The objectives of this work were to evaluate the rate of major depressive disorder (MDD) among precarious post-secondary students in the greater Paris region, to describe its risk factors, and to identify determinants for not seeking care. Methods: We conducted a multi-site, cross-sectional survey of post-secondary students attending a selection of 13 student foodbanks in the greater Paris region (France) between 30 November 2021 and 27 January 2022. This study had two complementary epidemiological and sociological components: a quantitative description of MDD through completion of a questionnaire performed through face-to-face or telephone interviews, and a qualitative assessment of the factors underlying MDD through in-depth follow-up interviews conducted among a sub-selection of students who participated in the first phase. Results: Among 456 students who participated in our survey, 35.7% presented with MDD. The risk of suffering from MDD was higher among women, students housed by third-parties, students reporting moderately to severely hungry and/or poor physical health. Students receiving material and/or social support were less likely to present with MDD. Among students who reported needing health care in the last year or since their arrival in France, 51.4% did not seek care. Conclusions: To address poor mental health among precarious students, policy action must jointly consider financial precarity, administrative barriers, housing, food security, physical health, and access to health services, especially mental health. Funding: The City of Paris, the Maison des Initiatives Étudiantes, the Regional Health Agency of Île-de-France, the Carasso Fundation, and the Caisse nationale des allocations familiales.